Japanese Beetle, Popillia japonica Newman (Insecta: Coleoptera: Scarabaeidae) - Jamba Gyeltshen; Amanda Hodges (EDIS)
The Japanese beetle, Popillia japonica Newman, is a widespread and destructive pest of turf, landscape, and ornamental plants in the United States. It is also a pest of several fruit, garden, and field crops, and has a total host range of more than 300 plant species. Adult Japanese beetles feed on foliage, flowers, and fruits. Leaves are typically skeletonized or left with only tough network of veins. The larvae, commonly known as white grubs, primarily feed on roots of grasses often destroying turf in lawns, parks, and golf courses. Currently the Japanese beetle is the most widespread pest of turfgrass and costs the turf and ornamental industry approximately $450 million each year in management alone (Potter and Held 2002). This document is EENY-350, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2005.